ANALISIS DAMPAK DEBU USAHA PENGGILINGAN PADI TERHADAP KAPASITAS VITAL PARU TENAGA KERJA DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG TAHUN 2011 - ARYASIH, I.G.A.M.; Mahardika, I Gede; Budiarsa Suyasa, I.W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
The grain grinding business unit is needed by the farmer to process the harvest but also in particular, it creates air pollution from its dusty materials. The worker or operator has a potential risk of being contaminated by the dusty materials and lungs vital capacity reduction. This research is aimed to analyze the effects of the grain grinding polluting dust to wards the lungs vital capacity of workers at Abiansemal in Badung District. This research is sort of an analytical observation with cross sectional design. The number of chosen samples is 32 workers with a total sampling method among 16 grain grinding business units. The data resources is a primary data which obtained using questionnaire, the measurement and observation include: the worker's characteristic (working term, age, and height), dust value, breath frequency and lungs vital capacity. The data is analyzed using regression statistic. The result of the research indicates that the amount of dust at the grain grinding business unit is around 10,0079-11,6151 mg/m3, working term is one to 44 years, age 22-62, and height 155-175 cm, the condition of the grinding room is 93,75% does not meet the ventilation standard, 100% is not provided with dust control tool, 97,75% does not provide mask and 93,75% is situated in a housing are. The conclusion of the research is that dust level, working term and height in particular has a significant correlation with lungs vital capacity (p < 0,05) but age does not have a significant correlation with the workers lungs vital capacity (p> 0,05). The higher level of dust makes the higher lungs vital capacity reduction, the longer working term makes the lower lungs vital capacity and the taller of workers height .indicates the higher workers lungs vital capacity. The impact of dusty materials of grain grinding business unit towards the workers is the decreasing of workers lungs vital capacity by the disorder of lungs restriction function ( 65,62%). It is suggested to the business owner to conduct technical controls. Workers are strongly recommended to put on mask, have sufficient nutrition supplies and workers with the age over 40 years should not work in j:his area. For the health department of Badung District should implement any efforts of K 3, and for other relevant departments which take a part in giving recommendation must consider a requirement to make it outside the housing area.
Keywords: grain grinding business, dust, lungs vital capacity reduction